2017
DOI: 10.1186/s12917-017-1079-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Swine Toxoplasmosis by PCR and Genotyping of Toxoplasma gondii from pigs in Henan, Central China

Abstract: Background Toxoplasma gondii, a widely prevalent protozoan parasite, causes serious toxoplasmosis infections in humans and other animals. Among livestock, pigs are susceptible to T. gondii infection. Despite Henan being one of the biggest pig-raising provinces in China, little information exists on the epidemiology of toxoplasmosis in this location. Therefore, we molecularly characterized DNA samples from pigs in Henan. A total of 1647 samples, including 952 from dead piglets, 478 from seriously sick fattening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 39 publications
0
3
1
Order By: Relevance
“…In this study, isolating T. gondii DNA from the homogenate of a large meat samples (50 gram or 5 gram meat for one swine) rather than using a small sample would increase PCR sensitivity. However, T. gondii DNA was not detected in the pork digestion fluids during this survey (81 tissue homogenate, which came from 2090 swine), which is less than our previously survey (2.06%, 34/1647) from tissue samples in Henan province by T. gondii B1 gene [21]. Our result indicated that the relative low density of T. gondii parasites in pork.…”
Section: Resultscontrasting
confidence: 71%
“…In this study, isolating T. gondii DNA from the homogenate of a large meat samples (50 gram or 5 gram meat for one swine) rather than using a small sample would increase PCR sensitivity. However, T. gondii DNA was not detected in the pork digestion fluids during this survey (81 tissue homogenate, which came from 2090 swine), which is less than our previously survey (2.06%, 34/1647) from tissue samples in Henan province by T. gondii B1 gene [21]. Our result indicated that the relative low density of T. gondii parasites in pork.…”
Section: Resultscontrasting
confidence: 71%
“…The dominant T. gondii genotype in China is ToxoDB#9 [ 38 ]. Several studies have identified T. gondii ToxoDB#9 in swine, domestic cats, and sheep in Henan Province [ 21 , 23 , 24 , 39 , 40 ]. However, only ToxoDB#225 T. gondii has been identified in Chinese cattle [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, only 1 out of 13 T. gondii- positive samples gave complete genotyping results at all 11 gene loci, and was identified to ToxoDB genotype #9, and two samples were genotyped at four and two genetic loci, respectively (Table 2). In China, ToxoDB genotype #9 is a predominant genotype, and has been found previously in a number of hosts in different regions including Henan Province [16, 23]. However, data on the genetic characterization of rabbit-derived T. gondii isolates in China are limited.…”
Section: Resultsmentioning
confidence: 99%